The Effect Of Solvency And Operational Efficiency On The Company Value Of The Restaurant, Hotel And Tourism Subsector On The Indonesia Stock Exchange In 2019-2024 - Putri Indah; Hety Budiyanti; Nurman (International Journal of Education Management and Religion, 2026)
The restaurant, hotel, and tourism sectors have an important role in supporting national economic growth in Indonesia, especially through job creation to encourage Gross Domestic Product (GDP) growth by driving other sectors such as transportation, agriculture, and the food and beverage industry so that the value of companies in this sector is important to consider. However, fluctuations in the company's value are considered not only influenced by profitability, but also by capital structure and operational efficiency that are not fully optimal. Therefore, the problems in this study are focused on how solvency affects company value, how operational efficiency affects company value, and how solvency and operational efficiency affect company value simultaneously. The purpose of this study is to analyze the influence of solvency on company value, analyze the effect of operational efficiency on company value, and test the effect of solvency and operational efficiency simultaneously on company value in the restaurant, hotel, and tourism sub-sectors listed on the Indonesia Stock Exchange. This study uses a quantitative approach with secondary data in the form of corporate financial statements obtained through the official website of the Indonesia Stock Exchange and analyzed using panel data regression. The results of the study show that solvency has a significant effect on the company's value, while operational efficiency has no effect and is significant on the company's value. However, solvency and operational efficiency simultaneously affect the company's value.